Rancang Bangun Aplikasi Edukasi Reproduksi Manusia Pada Pelajar SMPN 187 Jakarta Berbasis Android - Djunaedi, Bagas; Malabay; Yulhendri; Tjahjono, Budi (Fakultas Teknik Universitas Persada Indonesia YAI, 2025)
The implementation of education at SMPN 187 Jakarta is often limited to the use of PPT and RPP,causing the material to become monotonous and less interesting for students. Reproductioneducation is also often not delivered comprehensively, resulting in less than optimal studentunderstanding. To overcome this, an Android-based application was developed which aims toincrease students' understanding of reproductive health. This application provides educationalmaterial covering secondary and primary aspects as well as a test feature to measure studentunderstanding, making learning more effective and interactive. This application uses Flutter as amulti-platformframework andDart as an open source programming languagewithOOPconceptsthat are easy to understand. The application backend is managed with Laravel, functioning asBackendAPImanagement of themobile application.The prototypemethod is used in development,starting from collecting user needs to creating a design/prototype. The results of this research areas an educational application and learning support media for students at SMPN 187 Jakarta bymaking learning media flexible and efficient, with features for characters that help improvestudents' and female students' understanding of educational reproduction.